A Facile Hybrid Electrochemical-chemical Approach to Synthesize Prussian Blue from a Single Ferricyanide Solution. (1st May 2017) - Agarwal, Rahul; Sharma, Manoj Kumar
Graphical abstract: The interconnected pores present in the three dimensional bi-continuous ligament structures of NPAu can catalyse the dissociation of ferricyanide into free ferric ions leading to the formation of PB from single ferricyanide solution. Highlights: Electrochemical conversion of Au to NPAu. NPAu electrode chemically catalyses the decomposition of ferricyanide at the electrode-solution interface. Results in formation of PB by hybrid E-C technique. The growth of PB film on NPAu shows linear relation with the dipping time. The amount of the PB can be controlled by varying the time. Abstract: A facile hybrid electrochemical-chemical (E-C) methodology is demonstrated to synthesize Prussian blue (PB) on Au electrode from single ferricyanide solution in a two-step process: (i) electrochemical conversion of Au to nanoporous gold (NPAu) and (ii) chemical deposition of PB on NPAu from single ferricyanide solution (neutral pH) in dark, and the role of morphology of Au surface in chemical synthesis of PB is also explored. All the experiments with K3 [Fe(CN)6 ] are performed in dark to exclude the possibility of photochemical/photocatalytic synthesis of PB. Formation of PB is confirmed by cyclic voltammetry (CV), UV-Visible spectroscopy (UV-Vis.), energy dispersive X-ray spectroscopy (EDX), and surface morphology of NPAu film and PB deposited on NPAu is studied by scanning electron microscopy (SEM). The growth of PB film on NPAu shows linear relation with the dipping time and therefore, the amount of the PB deposited on NPAu can be controlled by varying the time. Formation of PB is not observed on Au and AuO electrodes on standing in freshly prepared K3 [Fe(CN)6 ] solution. Open circuit potential (OCP) measurements shows NPAu catalyses the dissociation of ferricyanide to ferric and cyanide ions on standing in freshly prepared 10 mM K3 [Fe(CN)6 ] solution. The ferric ions are reduced to ferrous ions by the water and ferrous ions immediately react with ferricyanide to form PB on NPAu.